An Example of Urban Change in Historical Context: Gedikpaşa - Özcan Şabudak (İnsan & Toplum)
Gedikpaşa has received more than its fair share of the damage wrought by the industrialization policies that influenced Turkey in almost every field in the second half of the twentieth century. As a result, Gedikpaşa, known as the residence of the past, has gone through a forced industrialization process. We can see in the case of Gedikpaşa how the relative advan- tages of some of its districts compared to certain areas of the Historical Peninsula turned into disadvantages over time, and that proximity to the city’s administrative and economic center is not always an advantage, and geographic location in this respect may be a burden. Therefore Gedikpaşa has ceased to be a place where different cultural identities live together and has become a place where different economic identities exist and have a mutual complementary relationship. Although it has lost the identity it once had, which was based on social inclusion, Gedikpaşa has not entirely lost its original identity. We can instead say that it has gone through a qualitative transformation. As a district where workplaces, public buildings and houses became nested within one another, Gedikpaşa is an example of the transformation historical districts underwent in the last century. In this study, I describe the social and spatial degradation process in the historic city area of Gedikpaşa created by industrialization. I examine the negative results of this process from the standpoint of traditional production and social structure, and make sug- gestions for their solution.